Pengembangan Agribisnis Bawang Merah di Dataran Tinggi Bersama Kelompok Wanita Tani Desa Wae Ri’i Kabupaten Manggarai - Rizki Adiputra Taopan; Polikarpus Payong; Onesimus Ke Lele; Fany Juliarti Panjaitan (Institut Pertanian Bogor, 2023)
The development of shallot agribusiness in the highlands, especially in WaeRi'i Village, Manggarai Regency, has not been optimal due to various obstacles such as the lack of farmer’s knowledge, the limited input production, and the lack of shallot agribusiness training. To solve the obstacles, community service is held to improve the knowledge, skills, and attitudes of Women Farmer Group members in the development of shallot agribusiness, in the highlands of WaeRi'i Village. In the early stages, it was found that all group members did not have in-depth knowledge and were still have technical and non-technical constraints in shallot agribusiness development. The implementation method is (1) identifying problems through interviews (2) agricultural extension related to group organizing, risk management, and risk prevention (3) shallot cultivation technical training (4) field assistance (5) agricultural marketing socialization (6) monitoring and evaluation. Community service gives a real positive impact which can be seen through the pre-test result of 6.73% and 16.16% post-test results. The success of the program can also be seen from the results of the monitoring and evaluation so that the general conclusion of shallot agribusiness development in the highlands with the Women Farmer Group has increased from the criteria of not being good to be good enough. Furthermore, it is hoped that there will be efforts to increase group capacity better than before in the future.